Nonedible thevetia peruviana oil for the synthesis of biobased thermosets and vitrimers with tunable mechanical properties - Olosho, Adebayo Isaac; Alam, Md Shafi; Sukumaran Nair, Kiran; Ambade, Ashootosh V.; Adekola, Folahan Amoo (ACS Applied Polymer Materials, 2024)
Current attempts to replace fossil-derived materials with vegetable oils for polymer production mainly rely on edible oils. This approach raises sustainability concerns due to potential food security risks. This report introduces the first in-depth examination of Thevetia peruviana oil (TPO) epoxidation, an easily accessible nonedible vegetable oil, utilizing diverse acidic ion-exchange resins as catalysts. It is followed by the development of vitrimers based on epoxidized oil (ETPO) with various dicarboxylic acid hardeners. Amberlite IRC120H emerged as the most effective catalyst for the epoxidation of the oil, allowing for repeated catalyst reusability for up to five cycles. An impressive relative oxirane conversion of 98.9% was achieved after optimization. DSC analysis revealed that among the diacids, 2,2'-dithiodibenzoic acid (DTBZ) has the lowest activation energy with ETPO. Additionally, the ETPO-DTBZ-based thermosets displayed exceptional solvent resistance and thermal stability, indicative of a high degree of cross-linked networks within the system. Mechanical analyses revealed that all aliphatic hardeners resulted in soft materials, while DTBZ resulted in thermosets with tensile stress and modulus of 15 and 843 MPa, respectively. Consequently, DTBZ-ETPO thermosets were successfully recycled, repaired, and reshaped with minimal changes in the mechanical properties. The shape memory of the thermosets was also established.
Keywords: biobasedvitrimers; environmental sustainability; epoxidizedThevetial peruviana oil; nonedible oil; Optimization; shape memory

Design, synthesis, and adhesive performance evaluation of DOPA-Functionalized polyurethane elastomers - Davis, Disiya; Alam, Md Shafi; Purushothaman Bindu, Bhadra; Lakshmi, Durga; N Muhammed, Hasin; Torris, Arun; Ambade, Ashootosh V.; Sukumaran Nair, Kiran (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2026)
Functional polyurethane (PU) hot-melt adhesives were developed through the incorporation of a dopamine-derived chain extender (DADO) into thermoplastic PUs. The DADO monomer was synthesized via a four-step route and successfully integrated into the PU backbone using a one-pot, two-step polymerization involving polycaprolactone-diol and 4,4 `-methylenebis(phenyl isocyanate). Spectral analyses confirmed the formation of urethane linkages and the effective incorporation of catechol moieties. Monomodal molecular weight distributions were obtained through size-exclusion chromatography with Mn ranging from 12,000 to 17,000 g/mol. Thermal analyses demonstrated two-step decomposition behavior and a progressive increase in glass transition temperature with increasing DADO content. Mechanical testing revealed that there was substantial improvement in the tensile strength of these materials from 1.34 MPa for unmodified PU (PU-0) to 14.3 MPa for PU-10. Adhesion performance exhibited a similar trend, with PU-10 attaining the highest lap-shear strength of 3.92 +/- 0.19 MPa on the Al substrate. PU-10 exhibited the highest lap-shear strength of 3.92 +/- 0.19 MPa on aluminum and superior underwater stability with a value of 2.78 +/- 0.47 MPa compared to other formulations. Overall, controlled incorporation of DADO significantly enhances properties, and PU-10 represents the optimal formulation for high-performance hot-melt PU adhesives.
Keywords: chain extender; dopamine; hot-melt adhesive; polycaprolactone diol; polyurethanes

Green synthesis of PLGA and fabrication of topotecan and thymoquinone dual anticancer drug loaded PLGA nanoparticles: a controlled release study for cancer therapy - Srilatha Cheekuramelli, Naga; Muhammed, Hasin N.; Garnaik, Baijayantimala; Sukumaran Nair, Kiran (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2026)
Cancer therapy is often hindered by poor solubility, low bioavailability, drug resistance, and tumor microenvironmental barriers associated with conventional chemotherapeutics. Polymeric nano-drug delivery systems offer a promising strategy to overcome these limitations, particularly for synergistic multi-drug delivery. In this study, a biodegradable and biocompatible PLGA copolymer (70:30, M-w approximate to 14,500) was synthesized by ring-opening polymerization using zinc proline complex as an initiator through a green route. The copolymer's potential for delivering topotecan (TPT), a water-soluble chemotherapeutic, thymoquinone (TQ), a poorly water-soluble chemotherapeutic, and their combination (TPT+TQ) for cancer treatment was investigated. These nanoparticles demonstrateda consistent particle size < 200 nm high encapsulation efficiency along with desirable controlled-release attributes. Moreover, they exhibited specific release characteristics and cytotoxic effects against HeLa cells, achieving an IC50 value of 20.88 M for the combination therapy (TPT+TQ). Additionally, cytocompatibility testing on L929 fibroblasts confirmed over 98% cell viability for blank PLGA nanoparticles. Additionally, confocal imaging studies confirmed efficient cellular uptake and nuclear localization of the nanoparticles. Overall, the PLGA based dual drug loaded nanoparticles presents a promising approach for targeted, synergistic co-delivery, potentially improving efficacy and reducing toxicity in cancer therapy.
Keywords: Biodegradation; dual drug-loading; PLGA copolymer; thymoquinone; Topotecan